Engraftment of peripheral blood mononuclear cells from human T-lymphotropic virus type 1 carriers in NOD/SCID/gammac(null) (NOG) mice - Takajo, Ichiro; Umeki, Kazumi; Morishita, Kazuhiro; Yamamoto, Ikuo; Kubuki, Yoko; Hatakeyama, Kinta; Kataoka, Hiroaki; Okayama, Akihiko (International journal of cancer, 2007)
The transmission of human T-lymphotropic virus Type 1 (HTLV-1) occurs mainly via breast-feeding, sexual intercourse and blood transfusions. After transmission, the HTLV-1 infection is predominantly maintained by cell-to-cell infection and clonal expansion; however, the details have not yet been clarified. To investigate how HTLV-1 infected cells act in an environment without an effective immune reaction, peripheral blood mononuclear cells (PBMCs) from asymptomatic HTLV-1 carriers were inoculated into nonobese diabetic/severe combined immunodeficient (NOD/SCID)/gammac(null) (NOG) mice, which have immunological dysfunctions of T- and B-lymphocytes and NK cells. Human mononuclear cells including both CD4+ and CD8+ T cells were found to have infiltrated into various organs, including the liver, kidney, spleen and lung, when the mice were sacrificed 1 month after inoculation. The copy numbers of HTLV-1 provirus detected in the tissue-infiltrating human cells were much higher than those in the original PBMCs from the carriers. The expression of HTLV-1 mRNA was demonstrated in the tissue-infiltrating cells by reverse transcriptase-polymerase chain reaction. Inverse-long polymerase chain reaction showed that the pattern of HTLV-1 proviral integration was different from that of the original carrier and that it varied among NOG mice inoculated with PBMCs from the same carrier. These results suggest the selective proliferation of particular clones of HTLV-1 infected cells in NOG mice. Alternatively, transmission and new integration of HTLV-1 from infected cells to noninfected cells might have occurred in an environment without an effective immune reaction. The NOG mouse is considered a good animal model for the patho-physiological study of HTLV-1 infection with immunodeficiency.